MEMAKNAI PEMANFAATAN HUTAN DALAM MENJAMIN KELESTARIAN LINGKUNGAN HIDUP DI PROVINSI PAPUA - Roni Sulistyanto Luhukay (Jurnal Hukum dan Bisnis (Selisik), 2021)
The relationship and ties between the Papuan forest environment and the indigenous Papuanscreate economic interests. This can be proven by the fact that Papua's natural environmentcontains enormous natural potential. The urgency of forest use by customary law communitiesis influenced by many factors, economic, social, political and cultural factors including thefailure of special autonomy for Papua Province, and the high minimum standard of welfare forindigenous Papuans, there are very crucial problems in the social economy, Weak supportinginfrastructure business, Weak human resources, aspects of production, management, capitaland investment, market access, access to information, technology and design, andcompetitiveness. The problem of forest utilization in ensuring environmental sustainability inPapua Province can be seen from the implementation in the environmental sector with theunavailability of knowledge of indigenous Papuans regarding local wisdom in terms ofprotecting natural resources and biodiversity and the weakness of human resources related toenvironmental impacts due to management. improper forest that has the potential for naturaldisasters and the absence of a healthy environment